Efektifitas Pengembangan Buku Ajar Berbasis Nilai-Nilai Karakter Multikultural Terhadap Keterampilan Berpikir Kritis Siswa - Sony Ari Wibowo; - Murtono; - Santoso; Sri Utaminingsih (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
This study aims to describe the effectiveness of multicultural-based learning to improve students' critical thinking skills in elementary schools. This is a Research and Development (R & D), with the steps of potential problems analysis, data collection, product design, design validation, design revisions, product trials, and product revisions. This research was conducted in grade IV in SD 1 Tritis and SD 1 Karangnongko, combined as the experimental group, while SD 1 Daren and SD 3 Nalumsari as a control group, all in Nalumsari District, Jepara Regency. The results showed the t-test results found that t arithmetic> T table is 8.994> 1699, the value data were analyzed with a significance level of 0.05. So, as the basis for decision making, it can be concluded that Ho was rejected and Ha was accepted. Thus, it can be concluded that multicultural-based learning is effective in improving the critical thinking skills of fourth grade students of elementary schools.